2022
DOI: 10.3390/rel13030198
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive Abuse in the Context of Clergy Sexual Abuse in the Catholic Church

Abstract: In a significant number of cases, clerical sex offenders impregnate their victims and force them into hiding, abortion, or adoption. This phenomenon is referred to in this paper as reproductive abuse. Clearly, most victims of reproductive abuse are adults, but even among minor victims of clerical child abuse, between 1 and 10 percent may have experienced reproductive abuse. On the basis of pertinent studies, this paper explores archival material on several dozen allegations of reproductive abuse in the context… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…However, the consequences may be seen mainly in people confronting the clergy's misconduct in forms of betrayed trust and psychological and physical harm. [31][32][33][34] It can be concluded that the religious world shared common terms in describing misconduct; the common attributes were extortion, misuse of authority, abusive behaviors, and breaking the vows. The antecedents were a lack of attachment to religiosity and dysfunctional families, negligence, and misuse of authority and power.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the consequences may be seen mainly in people confronting the clergy's misconduct in forms of betrayed trust and psychological and physical harm. [31][32][33][34] It can be concluded that the religious world shared common terms in describing misconduct; the common attributes were extortion, misuse of authority, abusive behaviors, and breaking the vows. The antecedents were a lack of attachment to religiosity and dysfunctional families, negligence, and misuse of authority and power.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Betrayed trust and psychological and physical harm were the expected consequences of misconduct. [30][31][32][33][34]…”
Section: Literature Reviewmentioning
confidence: 99%
“…While force obviously does occur within CSMAA events (see Kennedy 2009, pp. 13, 110, 123-24, 130, 144, 149-51;Reisinger 2022;The Pillar 2022), because of the power to groom and deceive, it does not seem to be as needed in religious contexts. Furthermore, however, there is also a more subtle form of force that can be used such as blackmail using professional/client-based in-depth knowledge of the client's private life.…”
Section: • Whether Subtly or Forcefullymentioning
confidence: 99%
“…These are mentioned here because they occur (for examples, see Kennedy 2009, pp. 13, 110, 123-24, 130, 144, 149-51;Reisinger 2022; The Pillar 2022). However, while these crimes are deeply heinous, of concern here are the contexts of CSMAA where distress and confusion exist because of grooming, consent doubt, and entrapment at the hands of powerful clergy in the context of adult vulnerability.…”
Section: Clergy Sexual Crimes Against Adultsmentioning
confidence: 99%
“…As mentioned by Schiavone and Gervais (2017), the level of religiosity in a country is proportional to the closed-mindedness toward certain issues. Some of the consequences include radical church teachings promoting Open Access: https://ejournal.papanda.org/index.php/edukasiana/ homophobia or hostility towards members of the LGBTQ+ community (Callaghan & van Leent, 2019), misogyny or discrimination against women (Beattie, 2018;Hogan, 2015;Reisinger, 2022), among others. These issues were even worse in earlier times (Greenberg, 1982), and their effects on society persist, though not to the same extreme extent.…”
Section: Introductionmentioning
confidence: 99%